ANALISIS KEMAMPUAN NUMERIK MATEMATIS SISWA SMP IT NURUL HUDA BATUJAYA KELAS VII PADA MATERI ARITMATIKA DASAR - Reza Nur Zaini; Sutirna Sutirna (IKIP Siliwangi, 2021)
The purpose of this research to describe the mathematical numerical ability of students class VII SMP IT Nurul Huda Telukbango in learning mathematics. This research uses descriptive qualitative research methods because they only want to know the mathematical numerical abilities of students at the school. The data analysis used in this research is using qualitative descriptive, data analysis and interviews. The instrument in this study used a multiple choice test instrument. Based on the research results of students at SMP IT Nurul Huda Telukbango have high to very high mathematical numerical abilities there are only 5 students, those who have moderate mathematical numerical abilities are 5 people, students who have low to very low mathematical numerical abilities there are 20 students.